The Effectiveness of Online Learning through WhatsApp Groups - Meidawati Suswandari; Yoel Octobe Purba (STAI Hubbulwathan Duri, 2022)
This study aims to determine the effectiveness of online learning through WhatsApp groups at an elementary school in Jaten. This study is a qualitative study that analyzes online learning conducted through WhatsApp groups. Data collection techniques in this study used interviews and documentation. Data analysis uses interactive data analysis, including data reduction, data display, and drawing conclusions. The results show that online learning through WhatsApp groups is less effective in achieving learning objectives. This is due to various factors, including 1) Students do not all have cellphones, and there are still many working parents. As a result, students have to wait for their parents to come home first. 2) Students have difficulty in doing assignments. 3) Less effective in increasing the learning independence of students. 4) Lack of captured material. 5) Students have difficulty in doing assignments. 6) Parents complain because of difficulties in explaining the learning material.